Live-In Family Enhancement (LIFE): a comprehensive program for healing and family reunification - Deane, Lawrence; Glass, Jenna; Vystrcil-Spence, Inez; Mignone, Javier (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2018)
Family enhancement is an approach to child protection that has been recommended by numerous reviews of child welfare practice. A recent example emerged from a comprehensive review of the child welfare system in Manitoba, Canada. The inquiry recommended that family enhancement be utilised in all child welfare cases, and be funded at levels reasonable enough to allow comprehensive support for families seeking to re-unify. Agency staff told the inquiry, however, that current resources permitted only limited service, for insufficient time, and for only a small percentage of families in care.An Indigenous agency in Manitoba, Metis Child, Family, and Community Services, has devised an innovative approach in which parents were fostered along with their children. This allows the agency to make a wide range of resources available to families on a 24-hour basis for 8-to-12-month periods. The costs do not appear to exceed those of regular fostering of children.This Live-In Family Enhancement (LIFE) program was extensively evaluated in 2015. The findings show a significant set of benefits to families such as stronger attachment between parents and children, improved parenting skills for caregivers, strengthened social support for families, newly acquired household management skills, successful completion of employment training, and significantly improved trust in social workers and the agency. Many of these factors are correlated, in research, with increased rates of family reunification. The paper documents these findings, and recommends that this approach be expanded for use in prevention as well as reunification.